Female friendship and fraternité in the prostitute memoir novels of eighteenth-century France - Allistaire Tallent (Theatrum Historiae)
This essay explores a long-neglected novel, La Cauchoise, ou Mémoires d’une courtisane célèbre (César Ribié, 1783) and its depiction of female homosocial relations. As the prostitute heroine and narrator tells of her successful and colorful career and her many relationships along the way, we discover that her relationships (sexual, professional, and amicable) with other women prove to be the most satisfying and beneficial to her. These relationships can be read as a female version of the Revolutionary principle of fraternité.